Endothelial Perturbation in Cystic Fibrosis - Romano, Mario; Collura, Mirella; Iapichino, Luciana; Pardo, Francesca; Falco, Angela; Chiesa, Pierluigi Lelli; Caimi, Gregorio; Davì, Giovanni (Thrombosis and Haemostasis, 2001)
Cystic fibrosis (CF) is characterized by a persistent inflammatory state, which can be secondary to chronic pulmonary infection and may affect vascular endothelium. We measured circulating levels of von Willebrand factor (vWF), tissue-plasminogen activator (t-PA), and P-selectin in 20 CF patients and 20 healthy subjects. vWF, t-PA and P-selectin levels were significantly higher in CF patients. Endothelial perturbation (> 2 SD increase in both vWF and t-PA) was present in 65% of CF patients. These patients displayed lower FEV1 values compared to individuals without endothelial perturbation and an inverse correlation between FEV1 and P-selectin levels was observed. Tumor necrosis factor- (TNF-) and interleukin (IL)-6 levels were also increased in CF patients and significant direct correlations were found between TNF- and vWF, t-PA or P-selectin levels. These results indicate that CF patients exhibit signs of endothelial dysfunction/perturbation, which are likely to be related to a persistent inflammatory state due to chronic pulmonary infection, and may play a role in the progression of this disease.
Keywords: Endothelium; cystic fibrosis; von Willebrand factor; tissue plasminogen activator; P-selectin